The Pentatricopeptide Repeat Proteins TANG2 and ORGANELLE TRANSCRIPT PROCESSING439 Are Involved in the Splicing of the Multipartite nad5 Transcript Encoding a Subunit of Mitochondrial Complex I . Issue 4 (23rd June 2014) - Colas des Francs-Small, Catherine; Falcon de Longevialle, Andéol; Li, Yunhai; Lowe, Elizabeth; Tanz, Sandra K.; Smith, Caroline; Bevan, Michael W.; Small, Ian
Abstract : Two splicing factors of the multipartite mitochondrial nad5 transcript are pentatricopeptide repeat proteins. Abstract: Pentatricopeptide repeat proteins constitute a large family of RNA-binding proteins in higher plants (around 450 genes in Arabidopsis [ Arabidopsis thaliana ]), mostly targeted to chloroplasts and mitochondria. Many of them are involved in organelle posttranscriptional processes, in a very specific manner. Splicing is necessary to remove the group II introns, which interrupt the coding sequences of several genes encoding components of the mitochondrial respiratory chain. The nad5 gene is fragmented in five exons, belonging to three distinct transcription units. Its maturation requires two cis- and two trans-splicing events. These steps need to be performed in a very precise order to generate a functional transcript. Here, we characterize two pentatricopeptide repeat proteins, ORGANELLE TRANSCRIPT PROCESSING439 and TANG2, and show that they are involved in the removal of nad5 introns 2 and 3, respectively. To our knowledge, they are the first two specific nad5 splicing factors found in plants so far.